Utility of reticulocyte haemoglobin content (CHr) in the diagnosis of iron deficiency anaemia in adult females (Panacea Journal of Medical Sciences, 2024)
Background: Iron deficiency anaemia is the most common nutritional deficiency to affect people of all age groups. It is frequently detected only in the late stages of the disease by haemoglobin estimates, peripheral smear and iron investigations. Reticulocyte haemoglobin content [CHr] is the newer parameter detected by most haematology analyzers, which is useful in detecting iron deficiency anaemia in the early stages, even before the development of symptoms of anaemia.Role of CHr in the diagnosis of iron deficiency anaemia. Aim – To evaluate the role of reticulocyte hemoglobin content in the diagnosis of iron deficiency anaemia in adult females. Settings and Design: Cross-sectional study at tertiary care hospital.Methods and Materials: A 2 year observational cross-sectional study was conducted at a tertiary care hospital, after Institutional Ethics Committee approval. Total 76 cases were selected in the study after informed consent. 48 were taken as test samples with hemoglobin level less than 10gm% and 28 were taken as controls with hemoglobin level more than 10gm%. EDTA samples were collected, and their complete blood count (CBC) was analyzed on a 5-part haematology analyzer, followed by analysis of the same sample on the retic mode to determine reticulocyte parameters. The mean, standard deviation and p value were used to evaluate the dataResults: Out of the total 76 patients, 48 were controls and 28 were test cases. Mean Hb in the test group was 7.27 gm% whereas mean Hb in the control group was 12.8gm%. As per the CHr cut-off value obtained by the ROC curve, the mean value for CHr was 22.12 pg in the test group and 27.3pg in the control group. Using the t-test, CHr had a strong positive correlation with the RBC indices.Discussion: The correlation of the CHr with haematological indicators used to detect iron deficiency anaemia was analyzed in the current study. CHr values in the test group (Hb 10gm%) were significantly lower than in the control group (p 0.05). Significant positive associations were found between CHr and several RBC parameters.